Neurological Manifestations of Mycoplasma pneumoniae Infection in Hospitalized Children and Their Long-Term Follow-Up - Kammer, Jessica; Ziesing, Stefan; Davila, Lukas Aguirre; Bültmann, Eva; Illsinger, Sabine; Das, Anibh M.; Haffner, Dieter; Hartmann, Hans (Neuropediatrics, 2016)
Objective In this retrospective study, we aimed to assess frequency, types, and long-term outcome of neurological disease during acute Mycoplasma pneumoniae (M. pneumoniae) infection in pediatric patients.Materials and Methods Medical records of patients hospitalized with acute M. pneumoniae infection were reviewed. Possible risk factors were analyzed by uni- and multivariate regression. Patients with neurological symptoms were followed up by expanded disability status score (EDSS) and the cognitive problems in children and adolescents (KOPKJ) scale.Results Out of 89 patients, 22 suffered from neurological symptoms and signs. Neurological disorders were diagnosed in 11 patients: (meningo-) encephalitis (n = 6), aseptic meningitis (n = 3), transverse myelitis (n = 1), and vestibular neuritis (n = 1), 11 patients had nonspecific neurological symptoms and signs. Multivariate logistic regression identified lower respiratory tract symptoms as a negative predictor (odds ratio [OR] = 0.1, p < 0.001), a preexisting immune deficit was associated with a trend for a decreased risk (OR = 0.12, p = 0.058). Long-term follow-up after a median of 5.1 years (range, 0.6–13 years) showed ongoing neurological deficits in the EDSS in 8/18, and in the KOPKJ in 7/17.Conclusion Neurological symptoms occurred in 25% of hospitalized pediatric patients with M. pneumoniae infection. Outcome was often favorable, but significant sequels were reported by 45%.
Keywords: Mycoplasma pneumoniae; encephalitis; cerebellitis; hypersomnia; transverse myelitis; children